PENYELESAIAN PERSELISIHAN ANTARA PEKERJA DENGAN PENGUSAHA DI LUAR PENGADILAN BERDASARKAN UNDANG-UNDANG NOMOR 2 TAHUN 2004 TENTANG PENYELESAIAN PERSELISIHAN HUBUNGAN INDUSTRIAL - Syah, Galang Abdurahman (Journal of Law ( Jurnal Ilmu Hukum ), 2018)
ABSTRACTÂ The type of research used by the author is normative legal research, the other name is doctrinal legal research which is also referred to as library research or document study because this research is carried out or aimed only at written regulations or other legal materials.Disputes between workers and employers occur due to several factors, namely internal factors and external factors. Factors originating from the internal, among others, are due to not exercising the rights and obligations of each party, the absence of openness from the management of the company. The principle of resolving industrial relations disputes according to Law Number 2 Year 2004 prioritizes deliberations for consensus through bipartite negotiations, as the first step that must be taken by the disputing parties before taking another mechanism.Awareness and the desire of the parties to really want to resolve the dispute by using mediation has a big role for the smoothness and success of the mediation itself.Â Keywords: Industrial Relations Disputes